Precarious Working Conditions and Exploitation of Workers in the Nigerian Informal Economy - Akinwale, Akeem Ayofe (Social Science Diliman: A Philippine Journal of Society and Change, 2014)
Situations in the informal economy expose workers to dangers without opportunity for hazard pay, thereby reflecting exploitation. Based on the Marxist theory of conflict, this paper examines the extent of precarious working conditions and exploitation of workers in the Nigerian informal economy. A total of 500 respondents randomly selected from various informal economy organizations participated in the survey conducted in Lagos State, Nigeria. The findings revealed that most of the respondents (76.4%) had worked for up to five years consecutively, followed by a few (18%), who had worked for up to ten years consecutively. Their monthly income ranged from 10,000 naira ($60) to 80,000 naira ($485). Their mean monthly income was 30,000 naira ($182). Most of them (73.5%) worked for 10 to 12 hours daily, while 26.5% worked for seven to nine hours daily. The experience of low pay with relatively long daily working hours shows the extent of exploitation in the Nigerian informal economy. Several background characteristics, such as gender, age, level of education, and marital status influenced the workers’ experience of precarious working conditions and exploitation. Therefore, there is an urgent need for a progressive workplace policy that can ensure decent work and adequate protection for workers in the Nigerian informal economy. Keywords: Alienation, exploitation, hazards, informal economy, working conditions, Lagos